Perkembangan Tanaman Kopi Di Indonesia - Pulungan, Abraham Ismail; Elvina, Tri Shinta; Syahbudin, Syahbudin; Putra, Gustiansyah Perdhana; Malona, Arga; Putra, Fuad Stiady; Salqaura, Siti Sabrina (Journal of Agribusiness, Social and Economic, 2025)
This study aims to explore descriptively the development of coffee plants in Indonesia. This research uses literature study and secondary data. Data mainly obtained from Coffee Statistics published by Indonesian Statistic Center. The results showed that the People's Plantation is the largest coffee plantation, with the highest production and highest productivity. Meanwhile, large state-owned companies and large private companies tend to experience a decrease in both the area of coffee plantations, their production, and productivity. In Indonesia, the provinces with the largest areas and high production followed by productivity are the provinces of South Sumatra, Lampung, Aceh, North Sumatra, and Bengkulu.